Career development among women academicians: a case study in selected Universities in Uganda - Hassan, Amina (Institute of Education, International Islamic University Malaysia, 2012)
Women are still underrepresented in higher education in Uganda. Few women continue their studies to establish their career as academicians and occupy senior academic positions in Ugandan universities. Therefore the purpose of the study was to understand the contributing factors towards career development of Ugandan women academicians in universities in Uganda. The study contributed to the literature on the experience of women academics in sub Saharan Africa, Uganda in particular. Specifically, it provided the contributing factors towards the career development of Ugandan women academics. The findings are a guide to women who have the will to build their career to high academia, and higher education in general. Qualitative method of study was used. Purposive sampling method was used to select 14 participants for the study. The researcher used in-depth interviews, open ended questionnaire, and researcher's diary as strategies for collecting data. Constant comparative method was used to analyze data. The findings revealed that the informants have a positive attitude towards their teaching career. The contributing factors towards career development of Uganda women academics include: personal factors; such as high career aspirations, interest, values, large networking base, and community service. The environmental factors include: the support by important people which comes from parents, teachers, mentors and spouses. The conducive institutional environment includes good schools, good work environment, sabbatical, and gender equity. Financial support which comes in the form of scholarships and research funds. The women have developed their career amidst challenges; balancing between home and career roles, negative society attitude, institutional politics, and limits in networking. For the women to overcome these challenges they have shown some coping strategies such as time management, proper planning, quality academic work, and family support. In conclusion, the findings support the belief that personal and environmental factors influence career development. Therefore women should be dynamic and institutions should provide conducive environment for women to develop their career.